1992
DOI: 10.1159/000236131
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Concomitant Nickel and Chromium Sensitization Model in the Guinea Pig

Abstract: Although nickel allergy is the most frequent contact hypersensitivity in man, reports on successful nickel sensitization in experimental animals are scarce. Chromium hypersensitivity, on the other hand, is readily induced in guinea pigs. In this study we set out to obtain reproducible nickel sensitization in guinea pigs, in order to establish an animal model for immunospecific tolerance and desensitization studies in which two non-cross-reacting metal allergens, chromium and nickel, could be studied simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…These results are in line with the view that the nickel and HEMA-specific T cell repertoires include different sets of T cell receptors, some of which also recognize other metal salts or methacrylate congeners, respectively. Up to now, studies on cross-reactivity patterns of haptenspecific T cells had to make use of animal models [13,56,57] or, alternatively, depended on the availability of long-term, haptenspecific T cell clones, generated from sensitized patients [14,16,18,54]. Indeed, previous results obtained in those studies showed that, upon Ni and HEMA-sensitization, guinea pigs show cross-reactions to Pd and methacrylate congeners, respectively [13,57].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with the view that the nickel and HEMA-specific T cell repertoires include different sets of T cell receptors, some of which also recognize other metal salts or methacrylate congeners, respectively. Up to now, studies on cross-reactivity patterns of haptenspecific T cells had to make use of animal models [13,56,57] or, alternatively, depended on the availability of long-term, haptenspecific T cell clones, generated from sensitized patients [14,16,18,54]. Indeed, previous results obtained in those studies showed that, upon Ni and HEMA-sensitization, guinea pigs show cross-reactions to Pd and methacrylate congeners, respectively [13,57].…”
Section: Discussionmentioning
confidence: 99%
“…Challenge reactions were recorded after 2, 4, 6, 12, 24, 48 and 72 h. The intensities of the reactions were evaluated by two independent observers, giving the degrees of erythema numerical values as follows: 0 = negative, 0.5 = faintly pink, 1.0 = pale pink, 1.5 = pink, 2 = red (4–6).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, experiments on already sensitized animals were unsuccessful [8], and the first attempt to induce tolerance in humans by feeding the allergen was unsuccessful [9 11]. However, Lowney [12] in 1971 was able to induce tolerance using low doses of dinitrochlorobenzene in a group of 101 healthy male adults [12][13][14][15][16], Recently, in a series of experiments on guinea pigs [17][18][19], it has been shown to be possible to induce persistent im mune tolerance to nickel and chromium by oral adminis tration prior to cutaneous sensitization. The authors of this work state that 'specific immune tolerance can be induced by timely oral contacts with metal allergens, and that full unresponsiveness is not broken, but rather strengthened, by repeated skin contacts with the allergens.…”
Section: Introductionmentioning
confidence: 99%